Enhancing the osteoblastic differentiation through nanoscale surface modifications. Issue 2 (31st October 2016) - Silva‐Bermudez, Phaedra; Almaguer‐Flores, Argelia; Garcia, Victor I.; Olivares‐Navarrete, Rene; Rodil, Sandra E.
Abstract: Human mesenchymal stem cells (MSCs) showed larger differentiation into osteoblasts on nanoscale amorphous titanium oxide (TiO2 ) coatings in comparison to polycrystalline TiO2 coatings or native oxide layers. In this article, we showed that the subtle alterations in the surface properties due to a different atomic ordering of titanium oxide layers could substantially modify the osteoblastic differentiation of MSCs. Amorphous (a) and polycrystalline (c) TiO2 coatings were deposited on smooth (PT) and microstructured sandblasted/acid‐etched (SLA) Ti substrates using a magnetron sputtering system. The surface roughness, water contact angle, structure, and composition were measured using confocal microscopy, drop sessile drop, X‐ray diffraction, and X‐ray photoelectron spectroscopy, respectively. The ∼70‐nm‐thick coatings presented a well‐passivated and uniform TiO2 (Ti 4+ ) surface composition, while the substrates (native oxide layer) showed the presence of Ti atoms in lower valence states. The polycrystalline TiO2 ‐coated surfaces (cPT and cSLA) showed the same cell attachment as the uncoated metallic surfaces (PT and SLA), and in both cases, it was lower on the rough than on the smooth surfaces. However, attachment and differentiation were significantly increased on the amorphous TiO2 ‐coated surfaces (aPT and aSLA). The amorphous coated Ti surfaces presented the highest expression of integrins and production of osteogenic proteins in comparison to the uncoated and crystalline‐coated Ti surfaces. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 498–509, 2017.